Synthesis and biological evaluation of longanlactone analogues as neurotrophic agents. Issue 4 (15th February 2018) - Reddy, Chada Raji; Tukaram, Amol Gorgile; Mohammed, Siddique Z.; Dilipkumar, Uredi; Babu, Bathini Nagendra; Chakravarty, Sumana; Bhattacharya, Dwaipayan; Joshi, Pranav C.; Grée, René
Graphical abstract: Evaluation of neurotrophic activity of longanlactone along with its analogues has been achieved for the first time. A total of 12-analogues have been prepared including C4-epimers. Highlights: Longanlactone, a natural pyrrole-lactone alkaloid, analogs were synthesized. Neurotrophic effects of Longanlactone analogs were studied for the first time. mRNA Fold change was observed in BDNF gene expression study of Longanlactone. Abstract: Longanlactone analogues were synthesized using a route featuring Friedel-Crafts acylation, Sonogashira coupling and 1, 3-dipolar cycloaddition reactions. Structure–activity relationships were investigated for neurotrophic activity. Compound6 was found to have the most potent neurotrophic activity among all the synthesized analogues in Neuro2a cells as evidenced by a battery of in vitro/cell based assays for assessment of neurogenic and potential neurotrophic activity including neurite outgrowth assay and real time PCR for popular markers of augmented neurotrophic activity. Compound6 might serve as a template for further development of highly effective neurotrophic molecules.